Finite element analysis of dynamic state metalworking technological system - Залога, Вільям Олександрович; Шаповал, Юрій Володимирович; Дрофа, Костянтин Андрійович (Technology audit and production reserves, 2016)
Based on the analysis of the literature it was found that with cutting and turning speed increase during processing (spindle frequency) resonant phenomena that significantly affect the performance of cutting tools and quality (roughness) of finished surface can occur. The aim of the work is to determine the dynamic characteristics of metalworking system on the design phase that is without a full-scale experiment. This paper describes a stand based on constructed 3D model of modernized machine tool mod. 1700VF30 (spindle frequency 10000 rev/min) and the method and algorithm of development of finite-element model of dynamic state of designed 3D models of machine tool is proposed. With the help of developed model the modal analysis of the machine tool mod. 1700VF30 using the method of finite elements that can let to detect the resonant frequencies of oscillations within any range of the setting of the cutting was made. The finite element method using ANSYS executed a complex research of amplitude-frequency characteristics of constructed 3D model depending on the speed of the spindle rotation and frequency at which resonance phenomena occurs. Adequacy of the developed analytical model of dynamic state of the elements of a manufacturing system based on the upgraded machine tool 1700VF3 was proved experimentally. Results, received with its help differ from the experimental ones less than for 5 %.